Antifungal Activity of Paenibacillus kribbensis Strain T-9 Isolated from Soils against Several Plant Pathogenic Fungi - Sheng Jun Xu (The Plant Pathology Journal, 2014)
The bacterial strain T-9, which shows strong antifungal activity, is isolated from the soils of Samcheok, Gangwondo and identified as Paenibacillus kribbensis according to morphological and taxonomic characteristics and 16S rRNA gene sequence analysis. The P. kribbensis strain T-9 strongly inhibits the growth of various phytopathogenic fungi including Botrytis cinerea, Colletotricum acutatum, Fusarium oxysporum f. sp. radicis-lycopersici, Magnaporthe oryzae, Phytophthora capsici, Rhizoctonia solani, and Sclerotium cepivorum in vitro. Also, the P. kribbensis strain T-9 exhibited similar or better control effects to plant diseases than in fungicide treatment through in vivo assays. In the 2-year greenhouse experiments, P. kribbensis strain T-9 was highly effective against clubroot. In the 2-year field trials, the P. kribbensis strain T-9 was less effective than the fungicide, but reduced clubroot on Chinese cabbage when compared to the control. The above-described results indicate that the strain T-9 may have the potential as an antagonist to control various phytopathogenic fungi.